Sistem Pengontrolan dan Monitoring Budidaya Sarang Burung Walet Berbasis Android - Cyntia Widiasari; Ryan Pratama; Wiwin Styorini (Jurnal Elektro dan Mesin Terapan, 2021)
In the cultivation of swallow nests, swallow breeders experience problems, especially in maintaining the temperature and humidity of the room in the wallet bird house. Swallow breeders must be able to maintain a stable temperature and humidity and maintain the safety of the swallow from owl pests. When the temperature is hot, the swallow room will become dry so that the nest becomes damaged and the swallow feels uncomfortable living in the nest. Based on this, a control and monitoring system for swallow nest cultivation based on Android was created. This system can help reduce the temperature and humidity in the swallow nest room using a dew machine that works automatically and the swallow room door can open/close automatically using an application on a smartphone. This system can work well if given a supply voltage of AC220V and DC12V. The dew machine will work (ON) if the temperature is above 29°C or the humidity is less than 70%. The sensor read data will be sent by the NodeMCU to the blynk server and displayed on the smartphone. The swallow room door can be opened or closed based on the light intensity value measured on the LDR sensor which is then sent to the NodeMCU to drive the motor driver and stepper motor. With this system, farmers are expected to be able to monitor and control the condition of swallow’s nests using the blynk application on smartphones in real time. Key words: Swallow's nest, temperature, humidity, swallow room door, dew machine, blynk application